Parallel algorithms - Casanova, Henri (Chapman & Hall/CRC numerical analysis and scientific computing, 2009)
Focusing on algorithms for distributed-memory parallel architectures, this book covers theoretical models of parallel computation, parallel algorithm design for homogeneous and heterogeneous platforms, complexity and performance analysis, and essential notions of scheduling.